Field data challenge predictions of universal crop pest proliferation under warming - Mia K. Lippey; Jay A. Rosenheim; Daniel Paredes; Richard Sharp; Daniel S. Karp; Rebecca Chaplin Kramer; Sara E. Emery; Colleen R. Miller; Emily K. Meineke (Proceedings of the National Academy of Sciences, 2026)
Models generated from laboratory-based thermal performance experiments predict that arthropod crop pest densities will escalate under rising temperatures. Conversely, natural enemies are predicted to decline under warming, exacerbating pest outbreaks. We tested these predictions using 141,562 field-year observations of 43 arthropod populations across spatial and temporal temperature gradients. Pests exhibited remarkable heterogeneity of responses to elevated temperatures, with some populations increasing and others decreasing. Natural enemies also showed variable responses to elevated temperatures, with partial support emerging for the hypothesis that natural enemies are more vulnerable to warming than pests. Laboratory-measured thermal performance and life-history traits failed to explain the variability of responses across taxa. Our findings challenge predictions of universal pest proliferation, highlighting the urgent need for species-specific monitoring approaches in agricultural climate adaptation.